Implementation of the Joyful Learning Method to Enhance Student Participation in Aqidah Akhlaq Learning at Islamic Elementary Schools - Ghanimah Ghanimah; Nur Aisyah (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
This study aims to describe the implementation  of the Joyful  Learning method in enhancing student participation in the Aqidah Akhlaq (Islamic Creed and Morals) subject, identify the supporting  and inhibiting  factors, and analyze the results of the implementation at MI Miftahul Ulum and MI Sirajul Ulum Opo-Opo Krejengan Probolinggo. The main problem addressed is the low level of student activity and interest in Aqidah Akhlaq learning, often attributed to conventional teaching methods and a lack of engaging media. This research adopts a qualitative approach using a multi-site case study design.  Data collection  involved  participatory  observation,  in-depth  interviews (principals, teachers, and students), and documentation. The collected data were analyzed using data reduction, data presentation, and conclusion drawing. The findings indicate that: (1) The implementation of the Joyful Learning method  was  carried  out  through  three  main  stages:  planning   (formulating objectives, selecting material,  preparing  lesson plans), execution (creating  a fun atmosphere, utilizing educational  games, songs, and storytelling), and evaluation (reflection and feedback). (2) The primary supporting factors include the teacher’s creativity and mastery of the method, the availability of innovative simple media, and full support from the school principal. Inhibiting factors include insufficient time  allocation  for  detailed  media  preparation,  limited  school  facilities  and infrastructure, and the challenge of managing large, highly energetic classes. (3) The  results  of   the  implementation   show  a  significant   increase  in  student participation,  evidenced  by  heightened  enthusiasm,  intrinsic  motivation,  and students' courage to ask questions, answer, and actively interact during the learning process, which positively impacts their understanding and internalization of Aqidah Akhlaq values.